Tantalum carbide / graphite composite material and preparation method thereof

By introducing a transition layer composed of graphite and tantalum carbide into the tantalum carbide/graphite composite, the coating peeling problem caused by the difference in thermal expansion coefficient is solved, which enhances binding force and stability and extends product life.

CN119306516APending Publication Date: 2025-01-14ZHEJIANG LIUFANG CARBON TECH CO LTD

Patent Information

Application Number
CN202411320654.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

During the preparation and use of tantalum carbide/graphite composites, the residual stress caused by the difference in thermal expansion coefficients is relatively large, which leads to the coating falling off and affects the service life of the product.

Method used

Using a tantalum carbide/graphite composite structure including a graphite matrix, a transition layer and a tantalum carbide coating, the transition layer consists of graphite and tantalum carbide. Tantalum carbide is filled in the pores of graphite and extends along the tantalum carbide coating toward the graphite matrix. , gradually reduce porosity and tantalum carbide content, and form a transition layer to enhance binding force and relieve thermal expansion stress.

Benefits of technology

Through the design of the transition layer, the bonding force between the coating and the substrate is significantly improved, the service life of the composite material is extended, and the sudden change in the thermal expansion coefficient is slowed down, the release of thermal shock stress is promoted, and the overall stability is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119306516A_ABST
    Figure CN119306516A_ABST
Patent Text Reader

Abstract

The invention discloses a tantalum carbide / graphite composite material and a preparation method thereof, and relates to the field of graphite / coating composite materials. The tantalum carbide / graphite composite material comprises a graphite matrix, a transition layer and a tantalum carbide coating, wherein the transition layer is connected with the graphite matrix and the tantalum carbide coating; the transition layer comprises graphite and tantalum carbide, pores of the graphite are filled with the tantalum carbide, and in the transition layer, the porosity of the graphite is gradually reduced in the direction from the tantalum carbide coating to the graphite matrix, the content of the tantalum carbide is gradually reduced, and the porosity of the tantalum carbide is gradually reduced in the direction from the tantalum carbide coating to the graphite matrix. At least part of tantalum carbide in the transition layer extends from pores of graphite to the tantalum carbide coating and is connected with the tantalum carbide coating. Therefore, a strong binding force is formed between the coating and the matrix, and the service life of the composite material can be prolonged; the transition layer can slow down mutation of the thermal expansion coefficient between the graphite matrix and the tantalum carbide coating, and stress release caused by thermal shock is promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of graphite / coating composite materials, in particular to a tantalum carbide / graphite composite material and a preparation method thereof. Background Art

[0002] Graphite disk for semiconductor is one of the key consumables in the epitaxial growth process of MOCVD (metal organic chemical vapor deposition) equipment. Graphite has excellent properties such as high temperature resistance, high thermal conductivity, and high high temperature strength. It is the preferred material for the base disk substrate for epitaxy. However, graphite material is easy to oxidize, corrode, and wear-resistant, and it is easy to produce powder, thereby polluting the epitaxial growth cavity environment and reducing the quality of epitaxial products. Therefore, there are defects in directly using graphite substrates for semiconductor epitaxial film growth chambers. To compensate for this defect, a protective coating can be coated on the surface of the graphite substrate to achieve performance optimization of graphite components.

[0003] Coating technology is a widely used surface treatment process, which enables the base material component to obtain or enhance certain target performance by coating a layer of metal, alloy, ceramic and other materials on the surface of the base material. At present, the mainstream coating preparation technologies mainly include: brushing method, embedding method, magnetron sputtering deposition method, ion beam assisted deposition method, pulsed laser deposition method, liquid phase pulse discharge deposition method, chemical vapor deposition method, etc.

[0004] Tantalum carbide (TaC) is an important high-temperature structural material with high strength, corrosion resistance and good chemical stability. It has a melting point of up to 3880°C and has excellent properties such as oxidation resistance, acid and alkali corrosion resistance, thermal shock resistance, and air flow erosion resistance. It also has low gas permeability and good chemical and mechanical compatibility with graphite materials, making it one of the most suitable materials for graphite substrate protective coatings.

[0005] However, the thermal expansion coefficient of tantalum carbide ceramic material is relatively large, about 8.29×10 -6 / K, while the thermal expansion coefficient of commonly used graphite substrates is usually 5×10 -6 / K, the difference in thermal expansion coefficient between tantalum carbide and graphite substrate leads to large residual stress in the preparation and use of TaC coating. When the peak shear stress at the coating interface is greater than the bonding strength of the coating, the coating will fall off, thus affecting the service life of the product.

[0006] Therefore, the current tantalum carbide / graphite composite materials and preparation methods thereof still need to be improved. Summary of the invention

[0007] The present invention aims to alleviate or solve at least one of the above-mentioned problems to at least some extent.

[0008] In one aspect of the present invention, the present invention proposes a tantalum carbide / graphite composite material. In some embodiments of the present invention, the tantalum carbide / graphite composite material includes a graphite substrate, a transition layer and a tantalum carbide coating, wherein the transition layer connects the graphite substrate and the tantalum carbide coating; the transition layer includes graphite and tantalum carbide, and the tantalum carbide is filled in the pores of the graphite. In the direction from the tantalum carbide coating to the graphite substrate, the porosity of the graphite in the transition layer gradually decreases, and the content of tantalum carbide gradually decreases. At least part of the tantalum carbide in the transition layer extends from the pores of the graphite to the tantalum carbide coating and is connected to the tantalum carbide coating. As a result, there is a strong bonding force between the coating and the substrate, which is conducive to extending the service life of the composite material; the transition layer can slow down the sudden change of the thermal expansion coefficient between the graphite substrate and the tantalum carbide coating, and promote the stress release caused by thermal shock.

[0009] In some embodiments of the present invention, the density of tantalum carbide in the transition layer gradually decreases along the direction from the tantalum carbide coating layer to the graphite substrate.

[0010] In another aspect of the present invention, the present invention proposes a method for preparing the aforementioned tantalum carbide / graphite composite material. In some embodiments of the present invention, the method for preparing the aforementioned tantalum carbide / graphite composite material comprises the following steps: (1) placing a graphite block material in a reaction chamber, heating it to a first temperature, the first temperature being 900°C-1000°C, the pressure being controlled at 10000Pa-50000Pa, and alternately introducing H2O or CO2 gas, the total time for alternately introducing the gas being 10min-30min; (2) at a second temperature, the second temperature being 1000°C-1800°C, the pressure being controlled at 1000Pa-70000Pa; a, introducing a first gas, wherein the first gas includes hydrogen, argon and a first tantalum source, and the time for introducing the first gas is 20min-240min, to form a graphite matrix and a transition layer; (3) at a third temperature, wherein the third temperature is greater than the second temperature, and the pressure is controlled at 1000Pa-70000Pa, introducing a second gas, wherein the second gas includes argon and a second tantalum source, and the time for introducing the second gas is 30min-300min, to form a tantalum carbide coating, wherein the transition layer connects the graphite matrix and the tantalum carbide coating. The tantalum carbide / graphite coating prepared by the above method has all the characteristics and advantages of the tantalum carbide / graphite coating described above, which will not be described in detail here; the above method is simple to operate, easy to implement, and is conducive to improving the yield of the product.

[0011] In some embodiments of the present invention, the third temperature is 1850°C-2400°C. At the above temperature, tantalum carbide has a fast growth rate, good crystallization quality, high raw material utilization rate, and the formed tantalum carbide coating has better performance.

[0012] In some embodiments of the present invention, the first tantalum source includes tantalum pentachloride, and / or the second tantalum source includes tantalum pentachloride. Tantalum pentachloride can be formed into tantalum carbide by chemical vapor deposition reaction, infiltrate into the pores of graphite to form a transition layer in step (2), and form a tantalum carbide coating in step (3).

[0013] In some embodiments of the present invention, in step (1), the number of times H2O gas is introduced is 3-4 times, and the number of times CO2 gas is introduced is 3-4 times. Thus, the pore characteristics of graphite can be better controlled, which is conducive to the subsequent filling of tantalum carbide material in the graphite pores.

[0014] In some embodiments of the present invention, in step (1), the flow rate of H2O gas is 5-50 sccm, and the flow rate of CO2 gas is 5-50 sccm. This is conducive to slow etching of graphite, so that the pore size in the graphite is appropriate, which is convenient for subsequent filling of tantalum carbide.

[0015] In some embodiments of the present invention, step (2) satisfies at least one of the following conditions: the flow rate of hydrogen is 1slm-50slm; the flow rate of argon is 1slm-50slm; the feeding rate of the first tantalum source is 3g / min-30g / min. This is conducive to the formation of tantalum carbide and filling it in the pores of graphite.

[0016] In some embodiments of the present invention, in step (2), the first gas further comprises propylene, and the flow rate of propylene is 10 sccm-2000 sccm. With propylene as the carbon source, propylene can react with part of the tantalum source to form tantalum carbide and deposit into the pores of graphite.

[0017] In some embodiments of the present invention, step (3) satisfies at least one of the following conditions: the flow rate of argon gas is 1slm-50slm; the feeding rate of the second tantalum source is 10g / min-50g / min. This is conducive to forming a dense tantalum carbide coating, thereby facilitating the extension of the service life of the graphite composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0019] Figure 1 A scanning electron microscope image of the tantalum carbide / graphite composite material in Example 1 of the present invention is shown;

[0020] Figure 2 shows a scanning electron microscope image of the composite material in Comparative Example 1;

[0021] Figure 3A scanning electron microscope image of the composite material in Comparative Example 2 is shown.

[0022] Description of reference numerals:

[0023] 1: Tantalum carbide coating; 2: transition layer; 3: graphite substrate. DETAILED DESCRIPTION

[0024] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention.

[0025] In one aspect of the present invention, the present invention provides a tantalum carbide / graphite composite material. In some embodiments of the present invention, reference Figure 1 The tantalum carbide / graphite composite material includes a graphite substrate 3, a transition layer 2 and a tantalum carbide coating 1, wherein the transition layer 2 connects the graphite substrate 3 and the tantalum carbide coating 1; the transition layer 2 includes graphite and tantalum carbide, and the tantalum carbide is filled in the pores of the graphite. In the direction from the tantalum carbide coating 1 to the graphite substrate 3, in the transition layer 2, the porosity of the graphite gradually decreases, and the content of tantalum carbide gradually decreases. At least part of the tantalum carbide in the transition layer 2 extends from the pores of the graphite to the tantalum carbide coating 1 and is connected to the tantalum carbide coating 1.

[0026] In the composite material, part of the tantalum carbide material covers the pores inside the graphite material, which is equivalent to forming a transition layer composed of graphite material and tantalum carbide material between the graphite material and the tantalum carbide coating material, which is conducive to slowing down the sudden change of thermal expansion coefficient between the graphite matrix material and the tantalum carbide coating material, and promoting the stress release caused by thermal shock; due to the presence of these tantalum carbide materials deep inside the graphite, the microscopic contact area between the coating material and the graphite material is significantly increased (the increase in contact area, on the one hand, can increase the chance of carbon atoms in the graphite matrix and tantalum atoms in the coating material to form carbon-tantalum bonds, thereby helping to improve the bonding force; on the other hand, the increase in van der Waals force between tantalum carbide molecules and graphite molecules also helps to increase the interaction force between the coating and the matrix material; finally, the addition of bonding force brought by tantalum carbide embedded in the graphite also contributes to the increased bonding force between the coating and the material, and also helps to increase the bonding force between the coating and the matrix material), a larger contact area brings a stronger interlayer bonding force, and whether the change in thermal expansion coefficient changes from sudden change to gradual change, or the bonding force between the coating and the matrix material increases, it helps to improve the life of the coating product. Along the direction from the tantalum carbide coating to the graphite substrate, the porosity of the graphite in the transition layer gradually decreases. After the tantalum carbide fills the pores in the transition layer, the tantalum carbide content on the side of the transition layer close to the graphite substrate is smaller, and the tantalum carbide content on the side close to the tantalum carbide coating is higher, which is closer to the performance of the tantalum carbide coating. In addition, the tantalum carbide in the transition layer extends along the pores of the graphite and connects with the tantalum carbide coating, which is beneficial to improve the bonding strength between the coating and the substrate.

[0027] In some embodiments of the present invention, the density of tantalum carbide in the transition layer 2 gradually decreases along the direction from the tantalum carbide coating 1 to the graphite substrate 3. As a result, the density of the transition layer on the side close to the graphite substrate is closer to the density of the graphite substrate, and the density on the side close to the tantalum carbide coating is closer to the density of the tantalum carbide coating, and the density also shows a gradual trend, which is more conducive to the gradual transition of graphite to tantalum carbide coating performance (for example, thermal expansion coefficient, etc.), thereby being more conducive to improving the bonding force between the coating and the substrate, alleviating the problem of coating peeling, and extending the service life of the composite material.

[0028] In another aspect of the present invention, the present invention provides a method for preparing the aforementioned tantalum carbide / graphite composite material. In some embodiments of the present invention, the method for preparing the aforementioned tantalum carbide / graphite composite material may include the following steps:

[0029] (1) Place a graphite block material in a reaction chamber, raise the temperature to a first temperature of 900°C-1000°C, control the pressure at 10000Pa-50000Pa, and alternately introduce H2O or CO2 gas, the total time for alternately introducing the gas being 10min-30min.

[0030] At the above temperature and pressure, H2O or CO2 gas can react with graphite, thereby improving the pore structure of the graphite block, so that the pores of the graphite block extend a distance from the surface to the inside, and the pore distribution density gradually decreases from the surface to the inside, which is conducive to the subsequent formation of tantalum carbide material deposited in the graphite pores and extending from the inside to the surface along the graphite pores, thereby improving the bonding force between graphite and tantalum carbide. The inventor found that if the same gas is used for etching, it is easy to form pores with larger pore diameters, and the tantalum carbide material formed later is not easy to fill the graphite pores, resulting in a decrease in the strength of the material. Alternating different gases can avoid the adverse effects of excessive graphite pores on the strength of the material.

[0031] In some embodiments of the present invention, the first temperature can be 900°C, 920°C, 950°C, 970°C or 1000°C, the pressure can be controlled at 10000Pa, 20000Pa, 30000Pa, 40000Pa or 50000Pa, and the total time for alternating gas introduction can be 10min, 15min, 20min, 25min or 30min.

[0032] In some embodiments of the present invention, in step (1), the number of times H2O gas is introduced may be 3-4 times, and the number of times CO2 gas is introduced may be 3-4 times. Thus, graphite can be etched by alternately introducing H2O gas or CO2 gas, so that the graphite pores show a trend of gradually decreasing porosity from the surface to the inside, and the pores extend from the surface to the inside, thereby facilitating the subsequent deposition of tantalum carbide material to extend along the pores of the graphite.

[0033] In some specific embodiments, H2O gas or CO2 gas may be introduced first, and the number of times H2O gas is introduced and the number of times CO2 gas is introduced may both be 3 times or 4 times. In other specific embodiments, H2O gas may be introduced first, and then CO2 gas may be introduced, and the number of times H2O gas is introduced is 4 times, and the number of times CO2 gas is introduced is 3 times. In still other embodiments, CO2 gas may be introduced first, and then H2O gas may be introduced, and the number of times CO2 gas is introduced is 4 times, and the number of times H2O gas is introduced is 3 times.

[0034] In some embodiments of the present invention, in step (1), the flow rate of H2O gas can be 5-50sccm, and the flow rate of CO2 gas can be 5-50sccm. For example, the flow rate of H2O gas can be 5sccm, 10sccm, 15sccm, 20sccm, 30sccm, 40sccm, 50sccm, etc., and the flow rate of CO2 gas can be 5sccm, 10sccm, 15sccm, 20sccm, 30sccm, 40sccm, 50sccm, etc. Thus, the pore characteristics of graphite are adjusted by reacting the pretreatment reagent H2O gas or CO2 gas with the graphite bulk material. The amount of pretreatment reagent introduced is low, and the pore distribution of graphite shows a distribution characteristic that the closer to the surface, the higher the porosity, and the closer to the inside, the lower the porosity; and at least part of the pores of the graphite extend a distance from the surface to the inside, which is conducive to the subsequent tantalum carbide material to be filled in the graphite pores by deposition and extend along the graphite pores.

[0035] Before placing the graphite block material into the reaction chamber, the graphite block material may be cleaned and dried. Cleaning can remove powder on the surface of the graphite block material, making it easier to process later.

[0036] (2) At a second temperature of 1000° C. to 1800° C. and a pressure of 1000 Pa to 70000 Pa, a first gas is introduced, wherein the first gas includes hydrogen, argon and a first tantalum source, and the time for introducing the first gas is 20 min to 240 min to form a graphite matrix and a transition layer.

[0037] When the first gas is introduced under the above conditions for reaction, the chemical reaction rate of the tantalum carbide growth process is slower at a lower temperature, the reaction activity of the raw materials is lower, and the tantalum carbide preferentially covers the pore positions on the graphite material with higher activity and diffuses into the pores. In the transition layer, at least part of the tantalum carbide extends outward from the pores inside the graphite.

[0038] In some embodiments of the present invention, the second temperature may be 1000° C., 1200° C., 1400° C., 1500° C., 1700° C. or 1800° C., the pressure may be controlled at 1000Pa, 5000Pa, 10000Pa, 30000Pa, 50000Pa or 70000Pa, and the time for passing the first gas may be 20min, 30min, 50min, 90min, 120min, 150min, 180min or 240min. Under the above conditions, the first tantalum source may react with hydrogen and graphite to form tantalum carbide, which is filled in the pores of the graphite.

[0039] In some embodiments of the present invention, the first tantalum source may include tantalum pentachloride (TaCl5). In some specific embodiments of the present invention, the first tantalum source may be tantalum pentachloride. Tantalum pentachloride may be formed into tantalum carbide by chemical vapor deposition reaction and filled in the pores of graphite.

[0040] In some embodiments of the present invention, in step (2), the flow rate of hydrogen can be 1slm-50slm, for example, the flow rate of hydrogen can be 1slm, 5slm, 10slm, 20slm, 30slm or 50slm. The above flow rate of hydrogen can promote the first tantalum source to fully react to generate tantalum carbide, thereby improving the utilization rate of the first tantalum source.

[0041] In some embodiments of the present invention, in step (2), the flow rate of argon gas can be 1slm-50slm, for example, the flow rate of argon gas can be 1slm, 5slm, 10slm, 20slm, 40slm or 50slm. Argon gas, as a carrier gas, can drive the first tantalum source to be quickly distributed in the reaction chamber; argon gas can also act as a protective gas, improve the safety of the reaction, and ensure the safety of equipment and operators.

[0042] In some embodiments of the present invention, in step (2), the feeding amount of the first tantalum source may be 3 g / min-30 g / min, for example, the feeding amount of the first tantalum source may be 3 g / min, 5 g / min, 10 g / min, 15 g / min, 20 g / min, 25 g / min or 30 g / min. This is conducive to forming tantalum carbide in a shorter time and filling the pores of graphite with tantalum carbide.

[0043] In some embodiments of the present invention, in step (2), the first gas may further include propylene, and the flow rate of propylene may be 10 sccm-2000 sccm, for example, the flow rate of propylene may be 10 sccm, 50 sccm, 100 sccm, 500 sccm, 1000 sccm, 1500 sccm or 2000 sccm. Thus, propylene may react with the first tantalum source as a carbon source to form tantalum carbide and deposit in the pores of graphite.

[0044] (3) At a third temperature, the third temperature is greater than the second temperature, the pressure is controlled at 1000Pa-70000Pa, and a second gas is introduced, the second gas includes argon and a second tantalum source, and the time for introducing the second gas is 30min-300min to form a tantalum carbide coating, and a transition layer connects the graphite substrate and the tantalum carbide coating.

[0045] Under the above conditions, a dense tantalum carbide coating can be formed, and the coating has a certain thickness, which can protect the graphite matrix, thereby extending the service life of the graphite composite material.

[0046] In some embodiments of the present invention, the pressure can be controlled at 1000Pa, 5000Pa, 10000Pa, 30000Pa, 50000Pa or 70000Pa, and the time for introducing the second gas can be 30min, 60min, 90min, 150min, 180min, 240min or 300min.

[0047] In some embodiments of the present invention, the third temperature may be 1850° C., 1950° C., 2000° C., 2200° C., 2300° C. or 2400° C. The tantalum carbide coating is grown by high temperature process, the tantalum carbide has fast growth rate, good crystal quality, high raw material utilization rate, dense coating, excellent coating performance, and better protective effect; the coating of required thickness can be formed in a shorter time, which is conducive to reducing production cost and equipment depreciation cost.

[0048] In some embodiments of the present invention, the second tantalum source may include tantalum pentachloride. In some specific embodiments, the second tantalum source may be tantalum pentachloride. Tantalum pentachloride may react with graphite in situ to generate a tantalum carbide coating.

[0049] In some embodiments of the present invention, in step (3), the flow rate of argon gas may be 1 slm-50 slm, for example, the flow rate of argon gas may be 1 slm, 5 slm, 10 slm, 20 slm, 30 slm or 50 slm. When the flow rate of argon gas is within the above range, the second tantalum source may be quickly distributed in the reaction chamber, thereby promoting the reaction.

[0050] In some embodiments of the present invention, in step (3), the feeding amount of the second tantalum source may be 10 g / min-50 g / min, for example, the feeding amount of the second tantalum source may be 10 g / min, 20 g / min, 30 g / min, 40 g / min or 50 g / min. This is conducive to forming a dense tantalum carbide coating with a suitable thickness in a shorter time.

[0051] In general, the tantalum carbide / graphite composite material prepared by the method proposed in the present invention has excellent performance, a strong bonding force between the coating and the substrate, and the coating is not easy to peel off; the transition layer can play a good transition role, so that the thermal expansion coefficient between the graphite substrate and the tantalum carbide coating presents a gradual trend, promotes the stress release caused by thermal shock, and improves the overall stability of the composite material. The method adds a pretreatment step before the coating process, and uses the pretreatment to create pores extending from the sample surface to the inside on the graphite substrate, and the pore distribution density gradually decreases from the surface to the inside; a layer of low-temperature tantalum carbide coating is added between the main tantalum carbide coating and the graphite substrate, and part of the tantalum carbide coating is inserted into the graphite along the internal pores of the graphite, so as to form a transition layer composed of tantalum carbide material and graphite material between the graphite substrate and the high-temperature tantalum carbide coating. The existence of the transition layer reduces the difference in thermal expansion coefficient between the substrate material and the coating material, so that the thermal expansion coefficient of the materials gradually transitions, and is also conducive to increasing the bonding force between the coating and the substrate material; the high-temperature tantalum carbide coating contributes to the main thickness of the coating material, is denser, and helps to provide better protection; the method is simple in steps, easy to operate, and the prepared product has a high yield.

[0052] The present invention will be described below by specific examples, and it will be appreciated by those skilled in the art that the following specific examples are only for illustrative purposes, and do not limit the scope of the present invention in any way. In addition, in the following examples, unless otherwise specified, the materials and equipment used are all commercially available. If in the following examples, specific processing conditions and processing methods are not clearly described, then conditions and methods known in the art can be used to process.

[0053] Example 1

[0054] (1) Put the cleaned and dried graphite parts into the reaction chamber, confirm that the airtightness of the reaction system meets the standard, and then start heating; first, heat to 900°C, control the pressure at 10000 Pa, alternately introduce 20 sccm of H2O and 20 sccm of CO2, and pre-treat the graphite parts sample for 10 min;

[0055] (2) The temperature of the reaction chamber was raised to 1200° C., and the pressure of the reaction chamber was controlled to 45000 Pa. After reaching a balance state, hydrogen, argon, tantalum pentachloride and propylene gas were introduced, wherein the flow rate of propylene was 50 sccm, the flow rate of argon was 5 slm, the flow rate of hydrogen was 5 slm, and the feeding rate of tantalum pentachloride was 20 g / min. After 30 minutes, the introduction of raw materials was stopped;

[0056] (3) The temperature of the reaction chamber is further increased to 2100° C., and the pressure of the reaction chamber is controlled to 40000 Pa. After reaching equilibrium, argon gas and tantalum pentachloride are introduced, wherein the flow rate of argon gas is 20 slm, and the feeding rate of tantalum pentachloride is 10 g / min. After 2 hours, the introduction of raw materials is stopped to obtain a tantalum carbide / graphite composite material.

[0057] Example 2

[0058] (1) Put the cleaned and dried graphite parts into the reaction chamber, confirm that the air tightness of the reaction system meets the standard, and then start heating; first, heat to 1000°C, control the pressure at 15000pa, alternately introduce 20sccm of H2O and 20sccm of CO2 to pre-treat the graphite parts sample, and the pre-treatment time is 20min;

[0059] (2) Raising the temperature of the reaction chamber to 1600° C., controlling the pressure of the reaction chamber to 40000 Pa and after reaching a balanced state, introducing hydrogen, argon, and tantalum pentachloride, wherein the flow rate of argon is 5 slm, the flow rate of hydrogen is 4 slm, the feeding rate of tantalum pentachloride is 30 g / min, and stopping the introduction of raw materials after 20 minutes;

[0060] (3) The temperature of the reaction chamber was further raised to 2200°C, and the pressure of the reaction chamber was controlled to 50000 Pa. After reaching equilibrium, argon gas and tantalum pentachloride were introduced, wherein the flow rate of argon gas was 20 slm, and the feeding rate of tantalum pentachloride was 15 g / min. After 1 hour, the introduction of raw materials was stopped.

[0061] Comparative Example 1

[0062] (1) Place the cleaned and dried graphite parts into the reaction chamber, and after confirming that the air tightness of the reaction system meets the standard, start heating;

[0063] (2) The temperature of the reaction chamber was raised to 1200° C., and the pressure of the reaction chamber was controlled to 45000 Pa. After reaching a balance state, hydrogen, argon, tantalum pentachloride and propylene gas were introduced, wherein the flow rate of propylene was 50 sccm, the flow rate of argon was 5 slm, the flow rate of hydrogen was 5 slm, and the feeding rate of tantalum pentachloride was 20 g / min. After 30 minutes, the introduction of raw materials was stopped;

[0064] (3) The temperature of the reaction chamber is further increased to 2100° C., and the pressure of the reaction chamber is controlled to 40000 Pa. After reaching equilibrium, argon gas and tantalum pentachloride are introduced, wherein the flow rate of argon gas is 20 slm, and the feeding rate of tantalum pentachloride is 10 g / min. After 2 hours, the introduction of raw materials is stopped to obtain a tantalum carbide / graphite composite material.

[0065] Comparative Example 2

[0066] (1) Place the cleaned and dried graphite parts into the reaction chamber, and after confirming that the air tightness of the reaction system meets the standard, start heating;

[0067] (2) raising the temperature of the reaction chamber to 2100° C., controlling the pressure of the reaction chamber to 45000 Pa and after reaching a balanced state, introducing argon gas and tantalum pentachloride, wherein the flow rate of argon gas is 25 slm, the feeding rate of tantalum pentachloride is 20 g / min, and stopping the introduction of raw materials after 50 min;

[0068] (3) Stop feeding the raw materials to obtain a tantalum carbide / graphite composite material.

[0069] The cross-sectional structures of the composite materials prepared in the examples and comparative examples were observed using a scanning electron microscope. Figure 1 , Figure 1 The SEM image of the tantalum carbide / graphite composite material in Example 1 is shown. Figure 1 It can be seen that the tantalum carbide / graphite composite material is stacked from bottom to top in sequence: a graphite substrate 3, a transition layer 2, and a tantalum carbide coating 1. The transition layer 2 includes graphite and tantalum carbide. The tantalum carbide is filled in the pores of the graphite. The tantalum carbide extends along the pores of the graphite and is connected to the tantalum carbide coating 1 on the surface. Figure 1 It can be seen that the tantalum carbide in the transition layer penetrates deep into the graphite material; and in the transition layer of the composite material prepared in Example 1, the porosity of the graphite gradually decreases along the direction of the tantalum carbide coating 1 pointing to the graphite substrate 3, and the content of tantalum carbide gradually decreases. The tantalum carbide / graphite composite material prepared in Example 2 also has the above characteristics.

[0070] refer to Figure 2 , Figure 2 The SEM image of the composite material in Comparative Example 1 is shown. Figure 2 It can be seen that since there is no pre-treatment of graphite, tantalum carbide penetrates into the interior of the graphite substrate according to the randomly distributed pores on the graphite substrate. Since the pores inside the graphite substrate are not artificially intervened, their distribution trend is spontaneously formed. The pore distribution is random and uncontrolled, and the ideal distribution form cannot be guaranteed. It is difficult to achieve a good buffering effect. The amount of tantalum carbide penetrating into the interior of the graphite substrate is small and the distribution is uneven.

[0071] refer to Figure 3 , Figure 3 The SEM image of the composite material in Comparative Example 2 is shown. Figure 3 It can be seen that when tantalum carbide is deposited directly under high temperature conditions, there is a clear boundary between the tantalum carbide coating and the graphite substrate, and the tantalum carbide does not penetrate deep into the graphite material.

[0072] In the description of the present invention, the orientation or position relationship indicated by the terms "upper" and "lower" etc. is based on the orientation or position relationship shown in the drawings and is only for the convenience of describing the present invention rather than requiring the present invention to be constructed and operated in a specific orientation. Therefore, it should not be understood as a limitation on the present invention.

[0073] In the description of this specification, the descriptions with reference to the terms "some embodiments", "other embodiments", "some specific embodiments", "other specific embodiments", etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment are included in at least one embodiment of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in a suitable manner in any one or more embodiments or examples. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of different embodiments or examples, unless they are contradictory. In addition, it should be noted that in this specification, the terms "first" and "second" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated.

[0074] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A tantalum carbide / graphite composite material, characterized in that: The tantalum carbide / graphite composite material comprises a graphite substrate, a transition layer and a tantalum carbide coating, wherein the transition layer connects the graphite substrate and the tantalum carbide coating; The transition layer includes graphite and tantalum carbide, and the tantalum carbide is filled in the pores of the graphite. In the direction along the tantalum carbide coating pointing to the graphite substrate, the porosity of the graphite in the transition layer gradually decreases, and the content of tantalum carbide gradually decreases. At least part of the tantalum carbide in the transition layer extends from the pores of the graphite to the tantalum carbide coating and is connected to the tantalum carbide coating.

2. The tantalum carbide / graphite composite material according to claim 1, characterized in that: Along the direction from the tantalum carbide coating layer to the graphite substrate, the density of tantalum carbide in the transition layer gradually decreases.

3. A method for preparing the tantalum carbide / graphite composite material according to claim 1 or 2, characterized in that: The following steps are involved: (1) placing a graphite block material in a reaction chamber, heating it to a first temperature of 900° C.-1000° C., controlling the pressure at 10000 Pa-50000 Pa, and alternately introducing H2O or CO2 gas, wherein the total time for alternately introducing the gas is 10 min-30 min; (2) at a second temperature, wherein the second temperature is 1000° C. to 1800° C. and the pressure is controlled at 1000 Pa to 70000 Pa, a first gas is introduced, wherein the first gas includes hydrogen, argon and a first tantalum source, and the time for introducing the first gas is 20 min to 240 min, to form a graphite matrix and a transition layer; (3) At a third temperature, the third temperature is greater than the second temperature, the pressure is controlled at 1000Pa-70000Pa, and a second gas is introduced, the second gas includes argon and a second tantalum source, and the time for introducing the second gas is 30min-300min to form a tantalum carbide coating, and the transition layer connects the graphite substrate and the tantalum carbide coating.

4. The method according to claim 3, characterized in that The third temperature is 1850°C-2400°C.

5. The method according to claim 3, characterized in that: The first tantalum source includes tantalum pentachloride, and / or the second tantalum source includes tantalum pentachloride.

6. The method according to claim 3, characterized in that In step (1), the number of times H2O gas is introduced is 3-4 times, and the number of times CO2 gas is introduced is 3-4 times.

7. The method according to claim 3, characterized in that In step (1), the flow rate of H2O gas is 5-50sccm, and the flow rate of CO2 gas is 5-50sccm.

8. The method according to any one of claims 3 to 7, characterized in that: Step (2) satisfies at least one of the following conditions: The flow rate of hydrogen is 1slm-50slm; The flow rate of argon gas is 1slm-50slm; The feeding amount of the first tantalum source is 3 g / min-30 g / min.

9. The method according to claim 8, characterized in that In step (2), the first gas also includes propylene, and the flow rate of propylene is 10 sccm-2000 sccm.

10. The method according to any one of claims 3 to 7 and 9, characterized in that Step (3) satisfies at least one of the following conditions: The flow rate of argon gas is 1slm-50slm; The feeding amount of the second tantalum source is 10 g / min-50 g / min.

Citation Information

Patent Citations

  • Method for preparing tantalum carbide coating on surface of graphite substrate and graphite device

    CN113549895A

  • Surface coating of graphite matrix as well as preparation method and application of surface coating

    CN115595659A

  • Method for preparing anti-oxidation coating on graphite surface

    CN115894080A

  • Graphite material with silicon carbide coating as well as preparation method and application of graphite material

    CN116590708A

  • Manufacturing method for single body and multi-layered polycrystalline silicon carbide parts, polycrystalline silicon carbide parts and shower head for plasma processing chambers

    KR102188258B1

Cited By

  • High-purity porous tantalum carbide ceramic as well as preparation method and application thereof

    CN120136575A

  • Large-size graphite disc based on microporous array of tantalum carbide coating and preparation method

    CN122667949A